THE MAIN TASKS OF EDUCATING YOUNG PEOPLE IN THE SPIRIT OF PROFESSIONAL PATRIOTISM - Turayev Jakhongir Anvarovich (Scholar Express Journal, 2022)
Along with pursuing a policy of peace, the Republic of Uzbekistan is committed to ensuring the security, peace and stability of its citizens. Under the United Nations Charter, the state exercises an inviolable right to defense, providing the state with military and defense power at a level of mental adequacy. Preparing young people for service in the Armed Forces of the Republic of Uzbekistan is a national task. In order to solve this problem, pre-service basic training, including training in civil defense, is a mandatory subject in the curriculum, and is taught in general education institutions, secondary special and secondary vocational education
Keywords: Forces of the Republic of Uzbekistan; military patriotic training; higher education institutions; patriotism